Binomial mania! (JEE mains question)

Probability Level pending

In the expansion of (a+b)^n , n >=5, the sum of 5th and 6th terms is zero. Then a/b equals,

6/(n-5) (n-5)/6 (n-4)/5 5/(n-4)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Vaibhav Gupta
Nov 2, 2015

Let n=5 because without putting n=5 we cant get 6th term ., 6th term = (5c5)( b^5) 5th term = (5c4)(a)(b^4) By equating 5th and 6th term, We get a/b= 1/5 And in the options put n=5

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...